Indirect Estimation Of Internal Migration In Algeria (1987-1998): An Assessment Of The Worksheet ‘csmigr’ - Abdelaziz , Siham (Journal of Social Sciences and Humanities, 2020)
The major difficulty of the quantitative analysis of internal migration for a country like Algeria, where no population register exists, and no law is forcing any person who moves to declare himself outgoing from his place of origin and incoming at the place of destination. Demographers have developed several estimation techniques, all based on simplifying assumptions and leading to rough estimates of migration flows. Therefore, indirect techniques could be a palliative to the shortcomings of direct estimates. CSMIGR the spreadsheet developed by the US Census Bureau is the main tool used in this paper, is precisely based on an indirect technique assuming implicit equivalent mortality across different regions of a country. This hypothesis can be raised if a reasonable estimate of the differential levels of mortality is available. In this paper, data from 2 Algerian censuses are used (1987 and 1998) and a correction of the output produced by CSMIGR will be proposed, based on differentials in regional mortality.